The Laxdœla Saga Its Structural Patterns - Arent Madelung, A. Margaret (UNC Studies in the Germanic Languages and Literatures, 1972)
This study is an unorthodox approach to the origin, historicity, and authorship of the anonymous Icelandic sagas. Following the publication of her translation of the "Laxdœla Saga", in this volume Madelung uses her deep knowledge of the text to demonstrate the literary quality and aesthetic structure of the work, especially the function of repetition. She shows that the Saga contains a historical-political analogy between the period in which the story is set (the eleventh century) and the saga-author's own time two centuries later. The apparently straightforward prose is camouflage, and the symbolism provides the key to the hidden analogy.